Teaching Speaking Through The Implementation of Story Telling Technique by Using Story-Telling - Purwatiningsih Purwatiningsih (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2014)
Learning a language especially English is expected to help students to be able to use it as a means of communication. Communicating is understanding and expressing information, thought and feeling, and expanding science, technology and culture. Communicating ability means being able to understand a discourse, namely being able to understand and produce spoken and written texts through the four language skills: listening, speaking, reading and writing this classroom action research was conducted to solve the students’ problems in speaking. It is to improve the students’ ability in speaking through story-telling technique using picture series in terms of content and delivery of the story. The design of this study is classroom action research which was conducted in two cycles consisting of six meetings. The subjects of this study were students of grade x-9 of MAN 2 Madiun in 2012/2013 academic year. The instruments to collect the data were observation checklists, field notes, speaking task measured using scoring rubrics, and questionnaire. The criteria of success were determined on the basis of the students’ participation in the teaching-learning process, the students’ speaking achievement in terms of score (telling a story individually), and the students’ responses to the implementation of story-telling technique using picture series. The finding of the study indicated that the implementation of the technique was successful in improving the students’ speaking ability, since the criteria of success were achieved. The first criterion was if 70% of the students participate or are actively involved in the teaching and learning process, and the data analysis confirmed that 84% of students were actively involved. Concerning the second criterion was if 70% of the students achieve the score greater than or equal to 75, the finding showed that 81% of the students already achieved scores greater than 75. The last criterion, if 70% of students have good responses to the implementation of the story-telling technique using puppets, the finding revealed that 89% of the students showed good responses to the technique. Implementing the story-telling technique using picture series in teaching speaking encompasses several procedures: 1) understanding the narrative text carefully, 2) understanding grammar and difficult words, 3) employing dictions based on its context, 4) discussing the text in groups, 5) using own sentences to deliver story, 6) avoiding mistakes by having picture series, 7) understanding the message or social value of the text, and 8) giving reward to enhance motivation.